ANALISIS INTERPRETASI PADA KARYA LUKIS SABRI MARBA YANG BERJUDUL ‘BADA MUDIAK’ - Heri Iswandi (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Art is a teaching of how humans construct an object into artwork. An artwork tries to present the problems in the environment that have meaning and significance. The type of artwork that will be analyzed by an aesthetic approach is a painting created by Sabri Marba that called bada mudiak. Bada mudiak (fish mudiak) the cluster of small fish into upstream river, bada motion always tidy and orderly, when the fish was suprised and move than the others fish will be follow it. All sides on the canvas depicted of bada mudiak. The artist exspresses the reality by means of symbolically to be conveyed. The analysis interpretation used to determine the meaning of  symbol that might be hidden in displayed of the artwork. Keywords: an analysis, interpretation, esthetic, painting.